Design and Characteristics of Islamic Economy: An Alternative Solution to the Global Crisis - Kamali, Kamali; Murtadho, Ali; Muhtadi, Ridan; Mi’raj, Denizar Abdurrahman (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The failure of the conventional economic system has been clear in world economic history. The occurrence of global crises is the result of the application of the interest system as a result of capitalism and the collapse of the Soviet Union as a tangible form of the failure of the socialist economic system led to the awareness of economists to review the two conventional systems and even require other alternatives that are more ethical and humane so that the same thing does not happen. The Islamic economic system meets these criteria. However, the Islamic economic system cannot be implemented without the support of knowledge about the characteristics and design of the Islamic economy. This study aims to explore the concepts of Islamic economics that are unique compared to the conventional economic system, the design of Islamic economics, and its implementation to anticipate the global crisis. The approach used in this research is a qualitative approach with a systematic literature review method. Data were obtained from scientific journals, books, and official documents relevant to the research topic. The analysis is done descriptively analytically to explore the main characteristics of Islamic economics and develop the system design. The results show that the Islamic economic system that offers a profit-sharing system, as applied in Islamic banks, is resilient in the face of the global crisis. In addition, the impact of the worldwide crisis that adversely affects poverty can be overcome through the instruments of Zakat, Infaq, Sadaqah, and Waqf, which are therefore essential to institutionalize and manage properly, transparently and accountably.